The Role of the Jewish Lobby Toward US Foreign Policy Making on the 2023 Israel-Palestine War (Case of AIPAC) (Hasanuddin Journal of Strategic and International Studies, 2024)
This paper examines the complex dynamics of the Israel-Palestine conflict, focusing on the role of interest groups, particularly the American Israel Public Affairs Committee (AIPAC) in shaping US foreign policy. The conflict, rooted in historical and territorial disputes, has seen recurrent escalations, most recently triggered by Hamas attacks on Israel. The United States, a longstanding ally of Israel, provides substantial financial and military aid, with AIPAC exerting influence on policymakers to maintain and strengthen this relationship. Through qualitative research methods and literature studies, the paper analyzes the impact of AIPAC's lobbying efforts on US policy responses to the Israel-Palestine conflict. The article finds that the AIPAC lobby is deeply rooted in US policymaking structures, ranging from vice-president, and higher-echelon staff, to parliament members. This article also finds that since 2021, AIPAC has developed its policy to participate in political campaign contributions. Understanding AIPAC influences, the authors note that ethical considerations are crucial to maintaining a strong and representative democracy in the United States. This paper recommends the US to refocus its national interest because such overly foreign influence on national policymaking has the potential to harm America's long-term relationships and interests in the Middle East if the US can’t make the barrier for foreign interference toward its national interests.